2010
DOI: 10.1080/01635581.2010.516874
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Wheat Aleurone Enriched With Probiotic Strains LGG and Bb12 Modulates Markers of Tumor Progression in Human Colon Cells

Abstract: Fermentation of dietary fiber by the microflora enhances the levels of effective metabolites, which are potentially protective against colon cancer. The specific addition of probiotics may enhance the efficiency of fermentation of wheat aleurone, a source of dietary fiber. We investigated the effects of aleurone, fermented with fecal slurries with the addition of the probiotics LGG and Bb12 (aleurone(+)), on cell growth, apoptosis, and differentiation, as well as expression of genes related to growth and apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
4
24
0
1
Order By: Relevance
“…These results are in line with former studies which revealed induction of apoptosis in LT97 cells by FS obtained from different raw nut varieties including macadamia nuts [18], or other dietary fiber sources producing butyrate as fermentation end product [29,30,38]. Again, no direct impact of different roasting conditions on apoptotic potential of fermented macadamia nuts could be observed in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…These results are in line with former studies which revealed induction of apoptosis in LT97 cells by FS obtained from different raw nut varieties including macadamia nuts [18], or other dietary fiber sources producing butyrate as fermentation end product [29,30,38]. Again, no direct impact of different roasting conditions on apoptotic potential of fermented macadamia nuts could be observed in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…has been shown to kill CRC cells through apoptosis in vitro via its metabolites, the SCFA, acetate and propionate [93,94]. However, synbiotics would be more active than probiotics alone in increasing the production of SCFA and consequently protect against CRC onset [10,95]. A possible explanation is that the interaction of the immunomodulating properties of probiotic bacteria and butyrate, which is more produced via fermentation of prebiotics, results in an upregulation of apoptosis [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Open Access Scan to access more free content compounds, [27][28][29][30][31][32][33][34][35] competition with putrefactive and pathogenic microbiota, [36][37][38][39][40] improvement of the host's immune response, [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] enhancement of natural killer cell cytotoxicity 56 and inhibition of interleukin (IL) 6 production in the colonic mucosa 57 counteracting cancer development by antiproliferative effects 58 via regulation of apoptosis and cell differentiation, [59][60][61][62][63][64][65][66][67] fermentation of undigested food [68][69][70][71][72][73] and inhibition of tyrosine kinase signalling pathways. 74…”
Section: Experimental Evidence Adhesion To the Gastrointestinal Mucosamentioning
confidence: 99%